Feasibility Study And Business Planning Of Rumahmakan.Online Digital Menu Whatsapp Ordering System - Lesmana, Fanji; Turgarini, Dewi (Gastronomy Tourism Journal, 2021)
Food delivery service business have increased rapidly in the era of the Covid-19 pandemic. People use new business model devices in their daily lives. E-commerce/platform of food delivery service is an integrated business system that started from the food provider to the food buyers. Â Commonly, the food delivery service platform set the "Cost of Technology" which is added to the calculation of Cost of Good Sold (CoGs/HPP). The cost of service burden the food provider.Â  Therefore, rumahmakan.online provides solution for food/restaurant providers, who have a personal digital menu. Food buyers can make orders via WhatsApp to the food provider/restaurant's WhatsApp number by using these platforms.Â